FRI0633 POSSIBLE ADVANTAGES OF 18F-FDG PET/CT-MR IN ADULT-ONSET STILL'S DISEASE: A STUDY FROM AN ITALIAN COHORT. (June 2019) - Bindoli, Sara; Rubin, Laura; Magnani, Fabio; Galozzi, Paola; Cecchin, Diego; Sfriso, Paolo
Abstract : Background: Adult-onset Still's disease (AOSD) is a systemic complex autoinflammatory disorder whose diagnosis is essentially clinical and necessitates the exclusion of potential mimickers. A specific diagnostic test to define the diagnosis or assess the disease activity is still not available. Objectives: To define the advantages of PET/MR in diagnosis and therapeutic response in AOSD patients and to assess a characteristic uptake pattern of 18 F-FDG at PET/CT-MR images of our cohort. Methods: 18 AOSD patients and 30 age- and sex-matched controls underwent 18 F-FDG PET/CT-MR between 2008 and 2018. A total of 44 PET/MR and 9 PET/CT performed at Padova University Hospital were analyzed. All AOSD patients were diagnosed according to Yamaguchi's criteria and had a regular follow-up at the Rheumatology Unit. Disease activity was evaluated using Pouchot's criteria. Uptake of affected organs was considered pathological when higher than liver uptake value. In order to analyze possible statistical differences of SUV ratios between the two groups, Mann-Whitney U-Test was applied. The variables considered were SUV ratios of spleen and bone marrow (BM). The SUV ratios were calculated between SUV of spleen-to-liver and of bone marrow-to-liver. We compared PET/MR and PET/CT of AOSD patients, evaluating possible statistical differences on SUV max ratios of bone marrow and spleen with Mann-Whitney U Test. To determine the strength and direction of the relationship between the continuous variables SUV ratios and Pouchot's score in our cohort Spearman's Rank Order Correlation Coefficient was applied. Results: All our patients presented areas of focal 18 F-FDG uptake. High and homogeneous accumulation of 18 F-FDG was observed at PET/CT-MR in spleen, BM, lymph nodes, pharynx, salivary glands and brown adipose tissue. PET/CT-MR of patients affected presented higher SUV ratios than controls. A statistically significant difference was observed for each SUV ratio in BM. In spleen p-values of 0.014, <0.001 and 0.002 were observed for SUV min ratio, SUV max ratio and SUV mean ratio respectively. Responders to therapy showed lower uptake at PET/CT-MR images during the follow-up. The SUVratios of PET/CT and PET/MR in AOSD were not significantly different. Conclusion: Our patients presented higher 18 F-FDG uptake at PET/CT-MR images compared to controls. Both PET/CT and PET/MR are not related to the disease activity expressed by Pouchot's score, however PET/CT-MR seems to be more reliable than Pouchot's score in disease activity assessment. PET/MR is more sensitive than PET/CT for the evaluation of BM in patients with low-disease activity and it is a better repeatable analysis compared to PET/CT because of less radiation dosage. References: [1] Sfriso P, et al. Adult-onset Still's disease: an Italian multicentre retrospective observational study of manifestations and treatments in 245 patients. Clin Rheumatol. 2016;35(7):1683-1689. [2] Yamashita H, et al. Clinical value of whole-body PET/CT in patients with active rheumatic diseases. Arthritis Res Ther.2014;16(5):423. [3] Jiang L, et al. Imaging characteristics of Adult-onset Still's disease demonstrated with 18F-FDG PET/CT. Mol MedRep.2017;16(3):3683686. Disclosure of Interests: None declared